Ten miles past normal - Dowell, Frances O'Roark (New York : Atheneum Books for Young Readers, 2011)
Fiction.
Keywords: Bands (Music) -- Fiction; High schools -- Fiction; Interpersonal relations -- Fiction; Schools -- Fiction